Genome sequencing and analysis of G. boninense, G. zonatum, G. miniatocinctum and G. tornatum towards understanding basal stem rot of oil palm - Nagappan, Jayanthi (2023)
Oil palm (Elaeis guineensis) is renowned as the golden crop of Malaysia and Indonesia for its’ high yields per hectare of land compared to other oil crops globally. Malaysia contributes 25.93% of the world’s palm oil supply with export revenue of RM73.25 billion in the year 2020. As with any other crop, oil palm faces challenges, such as pests and diseases in sustaining the oil palm plantation industry. In Malaysia, four Ganoderma species are commonly found in the oil palm plantations, whereby G. boninense (isolate PER71), G. zonatum (isolate POR69) and G. miniatocinctum (isolate 337035) are associated with high incidences of basal stem rot (BSR) disease, with the former being the most pathogenic of all species. The fourth species, G. tornatum (isolate NPG1) is a saprophyte. Besides being causal agents of BSR, G. boninense and G. zonatum are also causal agents of upper stem rot (USR) disease in Malaysia. For decades, studies have been conducted to understand the mode of infection and epidemiology, genetic diversity, and discover ways to curb these diseases from spreading to adjacent trees or new plantings. Most studies focused primarily on the host and host-pathogen interactions but not on the pathogen itself. Understanding the pathogen is essential and that too at the molecular level. With continuous developments in DNA sequencing technologies, PacBio single molecule-real time (SMRT) offers long reads with high accuracy to decipher many organisms. Although there are many extraction protocols available for Ganoderma species, the high molecular weight of good quality nucleic acid is a prerequisite of SMRTbell library construction. Therefore, the first objective of this study was to extract high quality genomic DNA for the four Ganoderma species required for PacBio sequencing. This study described modified DNA extraction protocols for G. boninense, G. zonatum, G. miniatocinctum and G. tornatum, and an RNA extraction protocol for G. boninense. The modified salting out DNA extraction protocol was suitable for G. boninense and G. miniatocinctum, while the modified high salt low pH protocol was suitable for G. tornatum. These modified nucleic acid extraction protocols were able to produce high quality DNA and total RNA of ~140-160 µg/g and ~80 µg/g of mycelia, respectively. As for G. zonatum, the Boehm protocol was the most rapid and efficient protocol with a yield of 208.95±4.52 µg DNA per gram of tissue. In the second objective, using the PacBio (Sequel platform) sequenced long read data, two draft genomes G. boninense the most pathogenic species, and G. tornatum, a saprophyte were assembled. The diploid aware assemblers FALCON and FALCON-Unzip phased assembled the two Ganoderma genomes generating ~67 Mbp and ~76 Mbp size genomes with 297 and 246 contigs for the former and latter species, respectively. Next, gene prediction was performed using four gene prediction pipelines on these two genomes, and MAKER2 was selected as the best pipeline generating 19,851 and 23,989 gene models, respectively. In the third objective, molecular markers were identified to distinguish pathogens from non-pathogens in oil palm plantations. This was performed using the four assembled Ganoderma genomes (454 sequencing technology). Species-specific simple sequence repeats (SSRs) were mined from the four Ganoderma genomes based on BUSCO (Benchmarking Universal Single-Copy Orthologs) and ortholog analysis. One hundred SSRs were synthesized and screened against the four Ganoderma species. Based on the screening results, 13 SSR markers were evaluated on 20 Ganoderma isolates collected from four states in West Malaysia. Data from the absence and presence of amplicons from the 25 Ganoderma isolates generated a phylogenetic tree. However, these 13 SSR markers were not able to distinguish the pathogenic isolates/species from the non-pathogens. Therefore, published internal transcribed spacers (ITS) were also used for species identification. For isolates with low quality ITS sequences, new ITS primers were designed based on the assembled G. boninense genome (PacBio) from this study. Molecular markers, together with morpho-taxonomy were able to facilitate the identification of Ganoderma isolates from West Malaysia. In the fourth objective, G. boninense culture was grown in limited carbon (C) and nitrogen (N) medium. This starved environment with minimal simple sugar and sawdust was to mimic as closely as possible to the field conditions. In response to the starved condition, differentially expressed genes (DEGs) in numerous metabolic pathways were identified, with four significant pathways explored in this study. The results provided first insights into possible genes that were up- and down-regulated in the pathways, namely secondary metabolite biosynthesis, carbohydrate metabolism, glycan metabolism and mycotoxin biosynthesis. A cocktail of enzymes was released by G. boninense to be associated with the degradation of cellulose, hemicellulose, lignin and pectin. The DEGs involved in the mycotoxin biosynthesis pathway are of interest, as they have not been reported in Ganoderma species. In the fifth objective, using comparative genome analysis genes associated with pathogenicity between the two Ganoderma species were identified. A workflow to detect small secreted proteins (SSPs) was used on the Ganoderma gene models of G. boninense and G. tornatum. A total of 18 candidate SSPs were identified in G. boninense, predicted to be involved in numerous functions associated with host-pathogen interactions.